Unsustainable agriculture and the fallow crisis: The case of farmers in the Apurimac and the Ene River Valley, VRAE - Bedoya Garland, Eduardo (2017)
This article is dedicated to the coca farmers of the VRAE. It shows that the abundance of «purmas» or secondary forest is due to the overuse of soils where coca is cultivated, the excessive use of modern or agrochemical inputs in these plantations and the traditional or empirical management of the cultivation of cacao and other annual crops. The high correlation between plot size and area in «purmas» is a true reflection of the fallow crisis in the VRAE. This crisis, however, is a result of the unsustainability of the aforementioned agricultural systems. The most important factors of this crisis are, on the one hand, an agricultural intensification of the cultivation of coca that degrades the soil and, on the other hand, an extensive use of the soil without a technological change in the case of legal crops. In both cases, the overall effect is the destruction of forests, deforestation and soil impoverishment.